Parity-time-symmetry enhanced optomechanically-induced-transparency - Li, Wenlin (Sci Rep, 2016)
We propose and analyze a scheme to enhance optomechanically-induced-transparency (OMIT) based on parity-time-symmetric optomechanical system. Our results predict that an OMIT window which does not exist originally can appear in weak optomechanical coupling and driving system via coupling an auxiliary active cavity with optical gain. This phenomenon is quite different from these reported in previous works in which the gain is considered just to damage OMIT phenomenon even leads to electromagnetically induced absorption or inverted-OMIT. Such enhanced OMIT effects are ascribed to the additional gain which can increase photon number in cavity without reducing effective decay. We also discuss the scheme feasibility by analyzing recent experiment parameters. Our work provide a promising platform for the coherent manipulation and slow light operation, which has potential applications for quantum information processing and quantum optical device.